Interstitial Space and Nation Language as Key Concepts in Latin American Literary Discourse (Islas, 2025)
Introduction: This paper offers a critique of Silviano Santiago’s concept of interstitial space (entre-lugar) and Kamau Brathwaite’s notion of nation language, with the aim of analyzing their potential and limitations within Latin American literary discourse.Methods: To carry out this analysis, a critical reading of these terms was conducted using Greimas’s semiotic square and the implications of the concept of language, respectively.Results: The findings revealed latent limitations within the concept of interstitial space, allowing for an argument concerning overdetermination and the possibility of multiple interstitial spaces. Furthermore, the study identified tensions between the code and nation language in the expression of the desiring subject within Latin American literary discourse.Conclusions: This study suggests that any positioning regarding the formation of Latin American literary discourse should adopt a multicausal approach that considers the tension between the language code and its non-signifying dimension.
Keywords: interstitial space; semiotic square; nation language; Latin American literary discourse